THE INTERPERSONAL RELATION TUTOR-STUDENT FROM THE PERSPECTIVE OF MAURICE TARDIF: A THEORETICAL REFLECTION - Letycia Sardinha Peixoto; Cláudia Mara de Melo Tavares; Donizete Vago Daher (Universidade Federal do Paraná, 2014)
This study is focused on the Interpersonal Relationship between tutors and students, emphasizing the interaction between these actors and its importance as a determining factor for professional education. The objective of this proposal is to reflect on this relationship, considering its influence on the pedagogical, social and cultural aspects of the teaching-learning process, exploring a theoretical perspective by Maurice Tardif on Knowledge and Human interaction. A strong, authentic and truthful exchange leads to the development of interpersonal skills, which is a component of social life, and acts in favor of mutual benefits in education and professionalization.